Answer:
Step-by-step explanation:
It’s 90 degrees hope this helps
Answer:
B'(- 2, 2 )
Step-by-step explanation:
Given the translation rule (x, y ) → (x + 3, y - 2 )
This means add 3 to the original x- coordinate and subtract 2 from the original y- coordinate, that is
B(- 5, 4 ) → B'(- 5 + 3, 4 - 2 ) → B'(- 2, 2 )
<em><u>Step-by-step explanation:</u></em>
FIRST, we want to understand every property:
Associative Property: The associative property states that you can add or multiply regardless of how the numbers are grouped so (5 + 4) + 3 = 5 + (4 + 3)
Commutative Property: Commutative is the one that refers to moving stuff around so 3 + 2 = 2 + 3
Additive Inverse Property: This is the number that when added to the original number, equals 0 or it's the opposite of the number so 5 <- is the original number and -5 <- is the additive inverse.
Simplify: Is just to add like terms, and make the equation the simplest.
1. ORIGINAL EXPRESSION
2. Additive Inverse Property
3. Commutative property
4. Associative Property
5. Simplify
6. Simplify
Answer:
x= -2
Step-by-step explanation:
Rational Function can be expressed as:
![\displaystyle \large{y = \frac{a}{p(x - b)} + q}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Clarge%7By%20%3D%20%20%5Cfrac%7Ba%7D%7Bp%28x%20-%20b%29%7D%20%20%2B%20q%7D)
Where b is our horizontal shift and q is our vertical shift.
For asymptotes, there are two types which are vertical and horizontal.
Vertical Asymtote is the value of -b itself or x = -b.
Therefore, from the functio:
![\displaystyle \large{y = \frac{10}{x + 2} }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%20%5Clarge%7By%20%3D%20%20%5Cfrac%7B10%7D%7Bx%20%2B%202%7D%20%7D)
Our vertical asymtote is x = -2